Alopecic aseptic nodule of the scalp in an 11-year-old girl. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
The alopecic aseptic nodule of the scalp is a benign disorder characterized by the presence of one or more nodules, hard or floating in the center of an alopecic area: the liquid possibly present in the nodules is always sterile. The nodules affect predominantly male adults and always regress with different therapies – antibiotics, intralesional corticosteroids – in times varying from weeks to years, with regression of the nodule and of alopecia. The nodules present histologically a mixed infiltrate, sometimes granulomatous in the deep dermis; in some cases the infiltrate necrosis produces pseudocyst cavities that justify the name of pseudocyst initially given to these nodules. Our case was characterized by the prepuberal age and by the female sex. In the literature there are only six cases of children aged 15 years or less, 4 males and 2 females (1, 2).